The effect of problem-based learning during the pandemic on self-confidence and social interaction of high school student - Siti Latifah Nursa'idah; Romy Faisal Mustofa; Egi Nuryadin (University of Muhammadiyah Malang, 2022)
The Coronavirus disease 2019 (COVID-19) pandemic has become an epidemic that has major impacts throughout the world, one of which is the change in the Indonesian education system from face-to-face learning to online learning. This study aims to determine the effect of online-based problem-based learning on the self-confidence and social interaction of students in class X MIPA at SMA Negeri 6 Tasikmalaya, West Java-Indonesia. This study uses the true experimental method. The population of this study is all classes X MIPA of SMA Negeri 6 Tasikmalaya for the 2020/2021 academic year. The samples of this study are class X MIPA 4 and class X MIPA 5, with as many as 36 students from each class. The instruments used are a self-confidence questionnaire and a social interaction questionnaire. The data analysis technique used is One-Way ANOVA with the Fcount of self-confidence (7.328) and social interaction (6.115). The results of data analysis and hypothesis testing concluded that there was an effect of problem-based learning on self-confidence and social interaction with a high category. A study using online-based problem-based learning must be supported by the readiness of students and teachers so that learning becomes effective. In addition, learning media such as Zoom meetings or Google Meet must be used.